2000
DOI: 10.1021/ol0058386
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis (and Alternative Proof of Configuration) of the Scyphostatin C(1‘)−C(20‘) Trienoyl Fragment

Abstract: [reaction--see text] Each of four diastereomers of structure 2, corresponding to the lipophilic side chain of scyphostatin (1), were prepared. Careful analysis of their NMR spectral data and comparison with those of the natural product corroborates the recently reported (Org. Lett. 2000, 2, 505) stereochemical assignment. A strategy for the stereoselective synthesis of 2 has been achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 21 publications
1
31
0
1
Order By: Relevance
“…One of the earliest methods for the preparation of terminally differentiated 2,4-dimethyl-1,5-pentane derivatives involves enzyme-catalyzed desymmetrization of 2,4-dimethyl-1,5-pentanediols (5). At the current level of development, however, the method suffers from low overall yields and long procedures for the synthesis of ␣-activated and -protected 2,4-dimethyl-1,5-pentanediols, which reportedly require six to eight steps and lead to 6-8% overall yields from diethyl ␣-methylmalonate and ethyl 2-bromo-2-methylpropionate for preparing the syn-dimethyl isomers (6,7). The preparation of the anti-dimethyl isomers is even less satisfactory, proceeding in seven to eight steps and leading to Ͻ2% overall yields (7).…”
mentioning
confidence: 99%
“…One of the earliest methods for the preparation of terminally differentiated 2,4-dimethyl-1,5-pentane derivatives involves enzyme-catalyzed desymmetrization of 2,4-dimethyl-1,5-pentanediols (5). At the current level of development, however, the method suffers from low overall yields and long procedures for the synthesis of ␣-activated and -protected 2,4-dimethyl-1,5-pentanediols, which reportedly require six to eight steps and lead to 6-8% overall yields from diethyl ␣-methylmalonate and ethyl 2-bromo-2-methylpropionate for preparing the syn-dimethyl isomers (6,7). The preparation of the anti-dimethyl isomers is even less satisfactory, proceeding in seven to eight steps and leading to Ͻ2% overall yields (7).…”
mentioning
confidence: 99%
“…Accordingly, several studies were conducted in the beginning of 2000 to determine the absolute configuration of scyphostatin and to synthesize related inhibitors, with low molecular weight, primarily as molecular tools to investigate the enzymatic mechanism of the various isoforms of sphingomyelinases (Saito et al 2000;Hoye and Tennakoon 2000;Izuhara and Katoh 2001;Runcie and Taylor 2001). It was found that scyphostatin inhibits shear stress-induced but not ceramide-induced activation of Src-like kinase and concomitant tyrosine phosphorylation of plasma membrane protein, thus confirming the hypothesis on the key role of NSMase and its downstream product ceramide in mechanosignaling (Czarny and Schnitzer 2004).…”
Section: Scyphostatinmentioning
confidence: 99%
“…The azide was reduced to the amine that was coupled with 332 (prepared as described by Hoye and Tennakoon [161]) and desilylated to give 351. Bromoetherifica-tion with NBS gave bromide 347, which was debrominated, oxidized and hydrolyzed to yield 348.…”
Section: Syntheses Of Scyphostatinmentioning
confidence: 99%